Quality characteristics and consumer acceptance of mussel (anodonta sp) snack prepared with different mussel meat composition - Desnizarianti '; Bustari Hasan; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was intended to evaluate quality characteristics and consumer acceptance of mussel snack formulated with different mussel meat composition. Mussel snack was prepared from fresh mussel meat, tapioca flour, sticky rice flour, chesse, egg, monosodium glutamat and backing soda. Three mussel snacks were prepared respectively by addition of 10%, 20% and 30% mussel meat. The snacks were evaluated for quality characteristics, consumer acceptance and proximate composition. The result indicated that the best sensory quality of the mussel snack was shown by that prepared with addition of 20% mussel meat; and the best consumer acceptance of the snack was produced by that made with addition of 10% mussel meat. Moisture, ash, protein and fat of the mussel snack made with addition of 10% mussel meat was 2,59%, 1,73%, 3,60% and 34,47% respectively; 20% mussel meat was 2,97%, 1,89%, 4,02%, 38,94% respectively and 30% mussel meat was 3,01%, 2,07%, 9,91% and 39,59% respectively.Keywords: Snack, mussel (Anodonta sp), quality characteristics, consumer acceptance, sensory evaluation, proximate composition